2017
DOI: 10.1002/er.3963
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of combustible waste gas as a supplementary fuel in coal-fired boilers

Abstract: Summary A system is proposed to use the combustible waste gas as a supplementary fuel in coal‐fired boilers. The combustion air can be partially or fully substituted by ventilation air methane or diluted combustible waste gases. The recommended volume fraction of combustible waste gas in combustion air is no more than 1.0%. The effect of waste gas introduction on thermodynamic parameters of boiler is evaluated through thermal calculation based on material balance, heat balance, and heat transfer principles. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Among these, coal and oil are mainly used. 35,36 In most power generation units, coal, oil, and coal + oil are used as fuels. Oil is used (short time) to start the boiler, as oil has more flammable characteristics than coal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, coal and oil are mainly used. 35,36 In most power generation units, coal, oil, and coal + oil are used as fuels. Oil is used (short time) to start the boiler, as oil has more flammable characteristics than coal.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, Macro-Precision, Macro-Recall, and Macro-F-measure 38,44 are used to check the effectiveness of the classification technique. The formulae for calculating the above-mentioned measures are given in Equation 24- (35).…”
Section: Evaluation Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al reported the results of a comparison between CFD and measured results for a 1000-MW USC utility boiler (Table ). The authors developed the thermal calculation code used in the study from a thermodynamic calculation applied to SC and USC boilers, which has been validated in many boilers in China, Russia, and Eastern Europe . The temperatures and heat absorption rates of the superheaters were compared, and they revealed a good similarity between the data from the industrial furnaces.…”
Section: Cfd Modeling Of Hele Coal Combustionmentioning
confidence: 99%
“…(B) Principal use, where VAM is the primary or even sole fuel. Category (A) includes those solutions in which the ventilation air would replace the atmospheric air introduced in known combustion methods [27]. Thus, [26] mentioned gas turbines, internal combustion engines as well as (basically primarily) coal-burning power plants and heating devices.…”
Section: A Contemporary Approach To Vam Utilizationmentioning
confidence: 99%